Parametric Resonance and Photogalvanic Currents in Layered TlGaSe2 Crystals - Odrinskii, A. P.; Seyidov, M-H. Yu.; Mammadov, T. G.; Alieva, V. B. (Pleiades Publishing Inc, 2017)
The results of the phenomenological study of the abnormal photoresponse kinetics in layered TlGaSe2 ferroelectric semiconductor have been discussed over the temperature range T of similar to 170-280 K corresponding to the paraelectric phase of crystal. Taking into account the alterations in the photoresponse kinetics temperature, the main mechanisms of anomalies caused by the spatial inhomogeneity of localized and nonlocalized charges in the bulk of the crystal have been assumed. The mechanism of parametric resonance is suggested to be favored by the photogalvanic currents in the crystal.
Keywords: Phase-Transitions; Spectroscopy; Behavior; Defects